Penerapan Undang-Undang Nomor 14 Tahun 2008 Tentang Keterbukaan Informasi Publik terhadap Kebijakan Pembangunan di Desa Tebas Sungai Kecamatan Tebas - Gindra (AL-SULTHANIYAH, 2024)
Public information is information that is produced, stored, managed, sent, and or received by a public body relating to the administration of the state. The focus of the problem in this research is how the application of Law No. 14/2008 on public information disclosure by the Village Government in Tebas Sungai Village, Tebas Sub-district, Sambas Regency. This type of research is qualitative research which is field research. The approach used in this research is empirical juridical. Based on the results of the research, it can be seen that the application of public information disclosure in Tebas Sungai Village has not been fully implemented, in accordance with Law Number 14 of 2008 concerning public information disclosure, Information Commission Regulation Number 1 of 2018 concerning village public service standards, Regional Regulations and Sambas Regent Regulations. The obstacles and constraints in implementing the Law are the unavailability of a budget for village public information management in the Tebas Sungai Village Government, in addition to limited resources and facilities in supporting public information management. So that the village government is not maximized in implementing Law Number 14 of 2008 concerning Public Information Disclosure.